Productive and Reproductive Efficiency of Ewes Kept on Tropical Pastures as a Function of the Suckling Lamb Treatments - K. L. S. M. Ferelli; C. C. B. F. Ítavo; L. C. V. Ítavo; G. T. dos Santos; M. I. L. Souza; G. K. A. de Melo; M. de M. S. Peres; N. da S. Heimbach; T. F. F. de S. Arco; E. S. de M. Soares; J. A. da Silva; P. C. G. da Silva; C. de Godoy; P. B. de Andrade; A. A. da S. Miguel (Tropical Animal Science Journal, 2023)
The aim of the research was to evaluate the productive and reproductive performances of ewes as a function of the supplementation offered to suckling lambs. The lambs were divided into two experimental treatments. Treatment (1) suckling lambs kept in pastures of Brachiaria-grass receiving mineral supplementation; and treatment (2) suckling lambs kept in pastures of Brachiaria-grass receiving concentrate supplementation in creep-feeding. Regardless of the nutritional treatment offered to the lambs, all matrices (female lambs and ewes) received 350 g of supplementation daily. Ewes from treatment-1 presented average 49 days to return to estrus. Ewes from treatment-2 presented, on average, 36 days to return to estrus. The body condition score (BCS) at weaning showed a significant difference between treatments. Ewes from treatment-1 presented a mean BCS of 1.75. Ewes from treatment-2 presented a mean BCS of 2.39. The other productive variables of lambs, such as weaning weight (kg), age at weaning (days), total weight gain (kg), and average daily gain of lambs, presented a significant difference between the nutritional treatments. Variables such as return to estrus and BCS were positively influenced by supplementation offered to lambs, which directly impacts the production efficiency and profitability of the production system. The lamb supplementation promotes indirect gains in the body condition score of ewes at weaning and, consequently, in the time to return of estrus in 13 days. Protein-energy supplementation in creep feeding to suckling lambs is recommended to improve the body condition score at weaning and decrease the return to estrus (days) of ewes. This nutritional tool is recommended to improve the supply of leaves and provide the best conditions for the selection and use of nutrients present in the leaves.